Land water availability altered by historical land use and land cover change - Tao Tang; Jun Ge; Junji Cao; Haiyun Shi (npj Climate and Atmospheric Science)
Abstract Anthropogenic land use and land cover changes (LULCC) have profound impacts on land water availability, defined as precipitation (P) minus evapotranspiration (ET), through biophysical pathways. However, such impacts have long been debated mostly due to either the inadequate consideration of the atmospheric feedbacks arising from the changes in circulations and background climate in observation-based studies or unrealistic representation of historical LULCC in idealized-simulation-based studies. To overcome these limitations, we use the latest simulations from multiple Earth system models to investigate the impacts of historical (1850–2014) and future (2015–2100) LULCC on P–ET. Here we show that historical LULCC caused an insignificant reduction in global P–ET, mainly in wet regions. Locally, P–ET tends to decrease (increase) in deforestation (reforestation) regions mainly due to the dominant role of precipitation. Approximately 3.8% of the global land area (5.1 Mkm2) even has experienced opposite regime shifts, in which negative (positive) P–ET becomes positive (negative). Under a medium-to-high warming scenario, however, reforestation is projected to decrease P–ET even over reforested areas. This study not only elucidates the hydrological effects of realistic LULCC with atmospheric feedbacks being fully considered, but also highlights that the relative importance of the local effects and atmospheric feedbacks varies with background climate changes. We stress that background climate changes and feedbacks due to LULCC should be considered when planning reforestation and other land-use policies.